TUGAS GEREJA SEBAGAI MISI KRISTUS DITINJAU DARI INJIL MATIUS 28:19-20 - Stafanus Sugiyanto (STT BIBLIKA JAKARTA, 2022)
The task of outreach or mission from the beginning had Christ commanded the disciples. When they were first called they were commanded in Matthew 28:19-20